Biology of Phalantha phalantha Drury (Lepidoptera : Nymphaliidae), a Pest of Populus deltowes Bartr - Ahluwalia, Rajani (Indian Forester, 2010)
Phalantha phalantha Drury is an orange colour butterfly with spotted wings. It starts emerging in the month of May and oviposits eggs on the leaves and green twigs. It has five larval instars with total larval period of 21-28 days. Fourth and the fifth larval instars are most harmful stages in which larvae feed voraciously and eat every part of the leaf. It completes its life cycle in 32-42 days in rainy season and completes 7-9 overlapping generations each year. June-August is the most active period of the pest and its population starts decliningfrom October end onwards.